Sex-related differences in serum Calprotectin, Acetate, and Zonulin as biomarkers for assessment of IBD - Noor Zuhair Bakheet NZ; Al-Qayim MAJ (Environment and Social Psychology, 2025)
Background: Inflammatory bowel disease (IBD), which includes Crohn’s disease (CD) and Ulcerative colitis (UC), is a chronic inflammation of the gastrointestinal tract. Early diagnosis and effective follow-up are essential for optimal outcomes. Objectives: This study aims to determine and compare the role of serum calprotectin, acetate, and zonulin as biomarkers for the assessment of IBD. Methodology: 96 patients aged 25-55 years with IBD diagnosis were based on clinical and endoscopic features at the Gastroenterology and Hepatology Specialized Hospital, located in Najaf, Iraq. Of these, 48 were healthy people (G1; men 24 and G2; women 24) and 48 were patients diagnosed with IBD disease (G3; men 24 and G4; women 24). The blood samples were analyzed using specific ELISA kits for calprotectin, Acetate, and Zonulin levels. Results: The level of serum calprotectin was significantly higher (P<0.05) in IBD patients than in healthy controls, and between genders of IBD patients, the serum calprotectin increased in men more than in women. However, the level of serum acetate was significantly lower (P<0.05) in IBD patients than in healthy controls, and between genders of IBD patients, the serum acetate increased in men more than in women. The level of serum zonulin was significantly higher (P<0.05) in IBD patients than in healthy controls, and between genders found that serum zonulin in women was higher than in men. Conclusion: We demonstrated that serum calprotectin has a significant increase in active disease and may be used as a biomarker for diagnosing and monitoring IBD patients in routine practice. A significant increase of serum zonulin, which is a biomarker of intestinal epithelial barrier dysfunction associated with decreased serum acetate, referred to as dysbiosis. Each parameter is associated with variables not related to the baseline disease, such as sex.